2018
DOI: 10.1021/acsanm.7b00160
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Graphene Oxide Nanoscrolls in Organic Solvents: Toward Scalable Device Fabrication

Abstract: In this work, formation of graphene oxide (GO) nanoscrolls in organic solvents was investigated upon dispersing GO nanosheets in organic solvents by sonication. It was found that, in some of the organic solvents, the single-layer GO sheets can effectively curl onto themselves to form the nanoscrolls that then sediment under gravity from the dispersion media. The sedimentation was monitored by UV−vis spectroscopy when the GO suspensions were left aside for different time periods after the sonication. The nanosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 64 publications
(185 reference statements)
1
18
0
Order By: Relevance
“…The high flexibility of the exfoliated InSe nanosheets makes them promising building blocks for constructing 1D architectures, which has been demonstrated by a class of 2D nanosheets, such as TMDs, graphene, and graphene oxide. As expected, distinct M-InSe nanoscrolls were produced from the as-prepared nanosheets, showing a hollow tube-like structure with diameters of 0.5–6.4 μm and lengths of 20–90 μm (Figure S13). A schematic illustration of the nanoscroll preparation process is shown in Figure a, following the solvent-assisted self-assembly. , An ultrathin nanosheet in the act of rolling was confirmed to be a monolayer according to the thickness of ∼1.1 nm extracted from the AFM image (Figure b).…”
Section: Results and Discussionmentioning
confidence: 60%
“…The high flexibility of the exfoliated InSe nanosheets makes them promising building blocks for constructing 1D architectures, which has been demonstrated by a class of 2D nanosheets, such as TMDs, graphene, and graphene oxide. As expected, distinct M-InSe nanoscrolls were produced from the as-prepared nanosheets, showing a hollow tube-like structure with diameters of 0.5–6.4 μm and lengths of 20–90 μm (Figure S13). A schematic illustration of the nanoscroll preparation process is shown in Figure a, following the solvent-assisted self-assembly. , An ultrathin nanosheet in the act of rolling was confirmed to be a monolayer according to the thickness of ∼1.1 nm extracted from the AFM image (Figure b).…”
Section: Results and Discussionmentioning
confidence: 60%
“…Unlike multiwalled nanotubes, GNSs possess an open morphology since the edges of their scrolled sheets are not fused . Scroll formation is controlled by two opposing energy contributions, where bending of the graphene sheets causes the elastic energy to increase, resulting in interactions in overlapping regions of the graphene sheet to reduce the free energy . The van der Waals and π‐π interactions between overlapping layers prevent GNSs from unrolling back into their planar morphology.…”
Section: Introductionmentioning
confidence: 99%
“…6 Scroll formation is controlled by two opposing energy contributions, where bending of the graphene sheets causes the elastic energy to increase, resulting in interactions in overlapping regions of the graphene sheet to reduce the free energy. 7 The van der Waals and π-π interactions between overlapping layers prevent GNSs from unrolling back into their planar morphology. Studies have shown that graphene as a nanofiller can increase the mechanical and thermal properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent-phase exfoliation of bulk BN can obtain single and multi-layer BNS in a highly polar solvent medium, such as N-methylpyrrolidone (NMP) [79,80] and dimethylformamide (DMF) [81]. However, it is essential that the energy required to exfoliate BN must be comparable to the solvent-BN interaction for exfoliation to occur first followed by scroll initiation later.…”
Section: Ultrasonic Exfoliationmentioning
confidence: 99%